SCIENTOMETRICS OF MARIA PENTELYUK’S CREATIVE HERITAGE IN THE FIELD OF UKRANIAN LINGVODIDACTICS (based on the periodical "Ukrainian language and literature at school" and the search system Google Scholar) (Journal of Information Technologies in Education (ITE), 2016)
This article deals with quantitative and qualitative analysis of references to scientific researches in articles of Full Professor Maria Pentylyuk, which were published during the 2013-2015 in the scientific and methodological periodical "Ukrainian language and literature at school", which is on the list of scientific professional editions of Ukraine, and in the search system Google Scholar, that indexes the full text publications of scientists and references on them in other academic literature. This article suggest the revealing of quotation indexes on scientist’s works, and there is also given an attempt to determinate Maria Pentylyuk’s publications, that have the greatest amount of quotations in the periodical "Ukrainian language and literature at school" and Google Scholar.
Keywords: scientometrics; scientometric base; quotation index; the search system Google Scholar; bibliometric profile; Maria Pentylyuk